The cut-off points of body mass index and waist circumference for predicting metabolic risk factors: findings from the China Kadoorie Biobank study - Meng, G; Yuxia, W; Jun, L; Du, H; Chen, Z (China Medicine Association, 2020)
Objective To assess the association of BMI and waist circumference (WC) with metabolic risk factors, and confirm the appropriate cut-off points of BMI and WC among Chinese adults.